Awareness and Availment of Services of Solo Parents as Provided in Republic Act 8972 - Broncano, Amalia B. (Future Science / FSH-PH Publications, 2023)
This research study was purposely conducted to determine the Level of Awareness and Extent of Availment of Services of Solo Parents as Provided in the Republic Act 8972. The concurrent-mixed method of research was utilized in the conduct of this study. From the results and findings of the study, the following conclusions were drawn: a) the level of awareness was interpreted as poor. This conclusion came from the following indicators: criteria for support as poor, qualifications of solo parent as high and the comprehensive package of social development and welfare services as very poor; b) extent of availment of services was interpreted as very low as the following indicators were assessed by the respondents as very low at all. These indicators are the livelihood development, counseling services, parent effectiveness services, flexible work schedule, educational benefits, housing benefits and medical assistance were all interpreted as very low; c) the difference in level of awareness and extent of availment among aspects across areas is significant. Proposed Intervention Plan was crafted to help the local government units particularly the City and Municipal Social Welfare and Development Offices enhance the level of awareness and extent of availment of benefits of solo parents.